2017
DOI: 10.1016/j.biochi.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Medium throughput biochemical compound screening identifies novel agents for pharmacotherapy of neurofibromatosis type 1

Abstract: The variable manifestation of phenotypes that occur in patients with neurofibromatosis type 1 (NF1) includes benign and malignant neurocutaneous tumors for which no adequate treatment exists. Cell-based screening of known bioactive compounds library identified the protein phosphatase 2A (PP2A) inhibitor Cantharidin and the L-type calcium channel blocker Nifedipine as potential candidates for NF1 pharmacotherapy. Validation of screening results using human NF1-associated malignant peripheral nerve sheath tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 20 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The experimental validation of the therapeutic effectiveness of drugs retrieved by NFFinder to treat NF1-associated MPNST was reported for HDAC inhibitors [ 28 ], cantharidin [ 29 ] and tamoxifen [ 30 ], and clinical trials have been suggested for all of them. The conclusion of our in-silico workflow ( Fig 2 ) with these experimental data confirms the predictive value of the MPNST vs. NF gene signature and its usefulness to identify robust biomarkers and therapeutic agents in neurofibromatosis disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental validation of the therapeutic effectiveness of drugs retrieved by NFFinder to treat NF1-associated MPNST was reported for HDAC inhibitors [ 28 ], cantharidin [ 29 ] and tamoxifen [ 30 ], and clinical trials have been suggested for all of them. The conclusion of our in-silico workflow ( Fig 2 ) with these experimental data confirms the predictive value of the MPNST vs. NF gene signature and its usefulness to identify robust biomarkers and therapeutic agents in neurofibromatosis disease.…”
Section: Resultsmentioning
confidence: 99%
“…The protein phosphatase 2A inhibitor cantharidin was found by screening from a library of 472 small bioactive compound library [29] and shown to avoid growth of NF1-associated MPNST cultured cells, though additional studies should clarify the relevance of cantharidin in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel drug targets for MPNST have also been suggested by others based on preclinical findings (Semenova et al ., ; Teicher et al ., ; Yamashita et al ., ). A recent drug screen of 63 sarcoma cell lines, including the two MPNST cell lines MPNST and ST8814, confirmed the heterogeneous responses among different soft tissue cancers (Teicher et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials have evaluated mitogen-activated protein kinase inhibitors for symptomatic plexiform neurofibroma[ 7 ]. Additionally, based on cell screening with a library of known bioactive compounds, we found that protein phosphatase 2, a plaque inhibitor and the calcium channel blocker nifedipine are potential therapeutic agents for NF1[ 18 ]. Identification of additional NF1 targeting molecules and good preclinical mouse models can provide a better understanding of the clinical features of NF1 and its treatment[ 19 ].…”
Section: Discussionmentioning
confidence: 99%